POSITIVISME LOGIS DALAM “LANGUAGE, TRUTH, AND LOGIC” KARYA ALFRED JULES AYER: SEBUAH PANDANGAN KRITIS - Fiandy Mauliansyah (Universitas Teuku Umar, 2017)
The essence of science in the body of logical positivism is based on the basis of the developmentof the exact sciences, so that the sciences developed are not always in line with the developmentof society. The objectivity that is concerned with the sciences is precisely molded in terms of theunfolding of the sciences, so it is absolute to use subjectivism which in principle will reflect itsobjectivity. Scientific truths are measured positivistically, in the true sense and the real must beconcrete, logical, accurate and rewarding. The effect behind it is that the abstract and qualitativedimensions of life are neglected and apart from observation. No doubt if the criticism andcorrection of positivism waged because of its naturalistic and diterministik. Humans are seenonly as dependent and not as independent variables.Keywords: Logical Positivism, Languange, Truth, and Logic